2021
DOI: 10.3390/metabo12010012
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Metabolites as Food Bio-Preservative: Innovation, Outlook, and Challenges

Abstract: Perishable food spoilage caused by fungi is a major cause of discomfort for food producers. Food sensory abnormalities range from aesthetic degeneration to significant aroma, color, or consistency alterations due to this spoilage. Bio-preservation is the use of natural or controlled bacteria or antimicrobials to enhance the quality and safety of food. It has the ability to harmonize and rationalize the required safety requirements with conventional preservation methods and food production safety and quality de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…However, LAB are a good alternative to chemicals in food application and agricultural product. The potential for preserving food products or extending their shelf life was previously confirmed (Baptista et al, 2020;Barcenilla et al, 2021;Mishra et al, 2022). Several compounds are responsible for antimicrobial activity, in particular antifungal activity such as organic acids, phenolic compounds, fatty acids, cyclic peptides, proteins and other miscellaneous compounds (El-Ghaish et al, 2017;Luz et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…However, LAB are a good alternative to chemicals in food application and agricultural product. The potential for preserving food products or extending their shelf life was previously confirmed (Baptista et al, 2020;Barcenilla et al, 2021;Mishra et al, 2022). Several compounds are responsible for antimicrobial activity, in particular antifungal activity such as organic acids, phenolic compounds, fatty acids, cyclic peptides, proteins and other miscellaneous compounds (El-Ghaish et al, 2017;Luz et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…), reuterin, exopolysaccharides, volatile compounds (for instance, diacetyl), antifungal peptides, hydrogen peroxide (H 2 O 2 ), nucleosides, and cyclic dipeptides [ 10 ]. In particular, this scoping review focuses on three of the main metabolites: reuterin (Reu), phenyllactic acid (PLA), and exopolysaccharides (EPSs) [ 11 ]. The decision to deal with this topic was the result of a thorough literature search (taken from various scientific databases) of the last two decades concerning these metabolites and their possible usefulness in the agro-food world; in order to have a clear overview, some keywords were used for this screening of scientific literature: “BioPreservation”; “Lactic Acid Bacteria”; “Fermentation”; “Food”; “Food Spoilage”; “Antifungal Metabolites”; “Phenyllactic Acid”; “Reuterin”; and “Exopolysaccharides”.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that compounds from spices, herbs, or tea can improve the quality parameters of LM; however, their extraction requires expensive technologies [ 28 , 29 , 30 ]. LAB are generally recognised as safe and offer plenty of advantages: (I) they can improve flavour and texture [ 19 , 31 ]; (II) due to their antimicrobial [ 32 , 33 ] and antifungal [ 33 , 34 ] metabolites, they can be used as biopreservatives to extend shelf lives [ 34 , 35 ]; (III) they have antioxidant properties [ 36 , 37 ]. It has also been published that lactobacilli strains have a broad range of applications, including meat processing [ 19 , 31 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%